2014
DOI: 10.1371/journal.pone.0097657
|View full text |Cite
|
Sign up to set email alerts
|

Human Hsp60 with Its Mitochondrial Import Signal Occurs in Solution as Heptamers and Tetradecamers Remarkably Stable over a Wide Range of Concentrations

Abstract: It has been established that Hsp60 can accumulate in the cytosol in various pathological conditions, including cancer and chronic inflammatory diseases. Part or all of the cytosolic Hsp60 could be naïve, namely, bear the mitochondrial import signal (MIS), but neither the structure nor the in solution oligomeric organization of this cytosolic molecule has still been elucidated. Here we present a detailed study of the structure and self-organization of naïve cytosolic Hsp60 in solution. Results were obtained by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 59 publications
7
52
0
Order By: Relevance
“…The values for GroEL and mitochondrial Hsp60 (used as standard protein) are of the same order of magnitude of those reported in literature [21,22]. The chromatograph we report in the Supporting Materials is the same previously reported in the paper written by some of us [14], because we used the same stock of commercial enzymes. All the experiments were conducted by diluting naïve Hsp60 from stock solutions to reach the concentration of 4.8 μM and dissolving GroEL in 20 mM Tris pH 8.0 and 10% glycerol (w/w) at 4.8 μM, too.…”
Section: Sample Preparationsupporting
confidence: 57%
See 2 more Smart Citations
“…The values for GroEL and mitochondrial Hsp60 (used as standard protein) are of the same order of magnitude of those reported in literature [21,22]. The chromatograph we report in the Supporting Materials is the same previously reported in the paper written by some of us [14], because we used the same stock of commercial enzymes. All the experiments were conducted by diluting naïve Hsp60 from stock solutions to reach the concentration of 4.8 μM and dissolving GroEL in 20 mM Tris pH 8.0 and 10% glycerol (w/w) at 4.8 μM, too.…”
Section: Sample Preparationsupporting
confidence: 57%
“…Higher protein concentrations were obtained with Vivaspin concentrators with a Polyethersulfone membrane and 10 kDa molecular weight cut-offs (Sartorius, Germany). Protein concentration for each experiment was determined by the area under a peak from the corresponding High Performance Liquid Chromatography (HPLC) chromatogram recorded at 280 nm [14]. The concentration determination was performed after Dynamic Light Scattering experiments on the samples, which showed that there were only the oligomeric species considered functional for chaperonins [5,11,14].…”
Section: Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…The other two exible linkers, connecting the N-and C-ending domain to the equatorial-intermediate domains, are from residues 23 to 26 and from 548 to 552. Taking advantage of recent ndings above mentioned, 11 and considering initial attempt to tting SAXS data (see Fig. S5 †), we have considered that, unlike GroEL, naïve-Hsp60 in solution can simultaneously be present as a mixture of tetradecamers and heptamers.…”
Section: Structural Analysis Of Naïve-hsp60mentioning
confidence: 99%
“…Various studies, published over the past several years, have demonstrated new subcellular locations and functions for Hsp60, describing it as a ubiquitous molecule with multiple roles in health and disease [42][43][44]. Moreover, detailed studies of the structure of Hsp60 have been reported that help understand the functions of this multifaceted molecule [45,46].…”
Section: Hsp60mentioning
confidence: 99%